Secondary school track selection of single-parent children: Evidence from the German Socio-Economic Panel - Philippe Mahler; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2005)
In present day Germany, one in seven children is raised in a single parent household. We investigate the effect of single parenthood on children's educational attainment, measured by the school track at the age 14, using ordered probit models. We study whether the effect of living in single parenthood during early or late childhood differs. Finally, we ask whether the family effect operates through resources - fewer income and parental time available for the child -, or through adverse effects on psychological well-being. The data used in this study are a nationally representative sample of 14 year old children drawn from the German Socio-Economic Panel.
Keywords: I21; J12; 330; school choice; educational attainment; ordered response model; Bildungsniveau; Alleinerziehende; Kinder; Bildungschancen; Schätzung; Deutschland